Odpowiedzi

2010-03-13T13:44:59+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10 |/(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9 |/3
x=3
c)10=4-2x
4-2x=10
-2x=10-4
-2x=6 |/(-2)
x=3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 |/(-2)
x=-1,5
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 |*(-1)
t=-7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)(x-7)-2(3x+5)=3
x-7-2x-10=3
x-2x-17=3
-x=3+17
-x=20 |*(-1)
x=-20
2010-03-13T13:48:05+01:00
A) -3x=2x-10
-3x-2x=10
-5x=10/:(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/:3
x=3

c) 10=4-2x
4-2x=10
-2x=10-4
-2x=6/:(-2)
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=1,5

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7/:(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/:(-5)
x=-4

2010-03-13T13:53:57+01:00
1)-3x-2x=-10
-5x=-10/:(-5)
x=2
2)2x+x=7+2
3x=9/:3
x=3
3)2x=4-10
2x=-6/:(2)
x=-3
4)-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-1,5
5)2x+2=x
2x-x=2
x=2
6)2t-3t-1=6
-t=6+1
-t=7/:(-1)
t=-7
7)-4-x=6-2x
-x+2x=6+4
x=10
8)x-7-6x-10=3
x-6x=3+10+7
-5x=20/:(-5)
x=-4